Comparison of SLAB design between BS 8110 and Eurocode 2 by using microsoft excel - Kamarul Ariffin, Mohd Mahpal (2010)
This project is to develop a program that able to analyze and design of reinforced concrete slabs using the application of spreadsheet Microsoft Excel. The analysis and design of slabs is in accordance with BS' 8110 Part 1: 1997 and Eurocode 2 - Design of concrete structures. Thus, this research focuses on the application of those design codes in the form of spreadsheets from Microsoft Excel for the purpose of analyzing and designing of reinforced concrete slab. Basically, the procedures in designing this element require numerous calculations in order to reach the most desired and economical design. Spreadsheet in Microsoft Excel has the capability of solving problems related to equations and formulas in a short time which makes design calculations and procedures easier. Besides that, Microsoft Excel is easily available and also presented in a user-friendly manner. A software has been developed with design procedures based on BS 8110 and Eurocode 2, which is the design of concrete slabs. Necessary checking such as deflection and crack control is also calculated by the software which helps to improve the accuracy of the design. The calculation done by the software was compared to manual calculation to ensure the reliability of this software. Results and conclusions show that this software fulfills the research objectives which are to develop software to aid designers in the designing using BS 8110 and Eurocode 2.